Tackling Multiculturalism or Strengthening Subcultures: the Macedonian Case - Dashtevski, Aleksandar; Gorjan Grncharovski (European Journal of Multidisciplinary Studies, 2018)
There is no general formula about what multiculturalism means exactly, and which rights it should encompass. It needs to be considered from various aspects. In the case of Macedonia, there are several ethnic groups in it that are in the vicinity of their home countries, which seek to protect their nationals from repression and discrimination. However, Albania is the most aggressive one and, in spite of direct contacts with Macedonian politicians from the Albanian ethnic group, it often interferes with the internal affairs of the Macedonian state. Although in Macedonia all collective rights are given to the ethnic minorities, including much more than what constitutes an international standard in Europe and in the world, in accordance with the Ohrid Framework Agreement of 2001, implemented in the state’s constitution, relations do not seem to be improving. On the contrary, other rights are constantly being sought, even higher than those set for the majority population in the country. On the other hand, the establishment of increased rights in the constitution and laws does not lead to coexistence and relaxation of the relations between the Macedonian and the Albanian communities. On the contrary, the Albanians are becoming ghettoized and live in separate communities, where they create their own subculture. Such behavior leads to greater segregation, which can create cantonization or federalization of the unitary state.